2012
DOI: 10.1016/j.ihj.2012.09.007
|View full text |Cite
|
Sign up to set email alerts
|

Door-to-balloon: Where do we lose time? Single centre experience in India

Abstract: With effective hospital strategies, the DTB time of 90 min can be achieved in majority of patients. The chief delay in DTB time in this study was due to a delay in obtaining consent and financial reasons.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 12 publications
2
23
1
Order By: Relevance
“…Investigation the correlation of time from initial assessment to emergency department until the onset of primary angioplasty with the final outcome in patients with acute myocardial infarction was evaluated in all studies included in the review. In majority of cases, primary angioplasty was achieved initiation time of less than 90 minutes from the initial assessment, resulting in better outcomes of patients (5,6,9,(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21). However, in case of performing culprit-vessel primary percutaneus coronary intervention before the unilateral or complete diagnostic angiography is associated with a statistically significant reduction in vascular access-to-balloon time, although the difference of 4-6 minutes is unlikely to be clinically relevant (22).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Investigation the correlation of time from initial assessment to emergency department until the onset of primary angioplasty with the final outcome in patients with acute myocardial infarction was evaluated in all studies included in the review. In majority of cases, primary angioplasty was achieved initiation time of less than 90 minutes from the initial assessment, resulting in better outcomes of patients (5,6,9,(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21). However, in case of performing culprit-vessel primary percutaneus coronary intervention before the unilateral or complete diagnostic angiography is associated with a statistically significant reduction in vascular access-to-balloon time, although the difference of 4-6 minutes is unlikely to be clinically relevant (22).…”
Section: Resultsmentioning
confidence: 99%
“…The studies that evaluated the impact of time from the initial assessment on emergency department until the onset of primary angioplasty, showed better direct and long-term clinical outcomes for patients with AMI STEMI diagnosis, which were submitted to PPCI within the indicated times. In particular, patients had better triennial outcome, with lower rates of composite death and congestive heart failure (11), lower probability of death in hospital (15) and lower overall mortality rates (9,12,19,21). In addition, the longest time was associated with disturbed myocardial perfusion but not with in-hospital mortality or with significant adverse cardiovascular and cerebrovascular events or other morbidity in the hospital (21).…”
Section: Effect Of Time Between Assessment and Angioplasty Onset On Pmentioning
confidence: 99%
See 2 more Smart Citations
“…[2] Another single-center study reported that 50% of the door-to-balloon time was spent in sorting out the financial process, which demonstrates the enormity of this problem. [12] Given cost constraints, poor patients frequently present to government hospitals where care is provided at a nominal charge; yet, except in large cities, care at government hospitals is often substandard due to deficient infrastructure and manpower. [9]…”
mentioning
confidence: 99%